Evaluating a Speech-Specific and a Computerized Step-Training-Specific Rhythmic Intervention in Parkinson's Disease: A Cross-Over, Multi-Arms Parallel Study - Rösch, Anne Dorothée; Taub, Ethan; Gschwandtner, Ute; Fuhr, Peter (Frontiers in Rehabilitation Sciences, 2022)
BACKGROUND: Recent studies suggest movements of speech and gait in patients with Parkinson’s disease (PD) are impaired by a common underlying rhythmic dysfunction. If this being the case, motor deficits in speech and gait should equally benefit from rhythmic interventions regardless of whether it is a speech-specific or step-training-specific approach. OBJECTIVE: This intervention trial investigated the effects of two rhythmic interventions on speech and gait. These rhythmic interventions are similar in terms of intensity and frequency (i.e. 3x per week, 45 minutes-long sessions for 4 weeks in total), but differ regarding therapeutic approach (rhythmic speech vs. rhythmic balance-mobility training). METHODS: This study is a cross-over, parallel multi-arms, single blind intervention trial, in which PD patients treated with rhythmic speech-language therapy (rSLT; N = 16), rhythmic balance-mobility training (rBMT; N = 10), or no therapy (NT; N = 18) were compared to healthy controls (HC; N = 17; matched by age, sex and education: p > .82). Velocity and cadence in speech and gait were evaluated at baseline (BL), 4 weeks (4W-T1), and 6 months (6M-T2) and correlated. RESULTS: Parameters in speech and gait (i.e. speaking and walking velocity, as well as speech rhythm with gait cadence) were positively correlated across groups (p < .01). Statistical analyses involved repeated measures ANOVA across groups and time, as well as independent and one-samples t-tests for within groups analyses. Statistical analyses were amplified using Reliable Change (RC) to calculate clinically true significant changes due to the treatment on a patient individual level. Intervention groups improved across variables and time (total Mean Difference: 3.07 [SD 1.8]; 95% CI .2 – 11.36]) compared to the NT group, whose performance declined significantly at 6 months (p < .01). HC outperformed rBMT and NT groups across variables and time (p < .001); the rSLT performed similarly to HC at 4 weeks and 6 months in speech rhythm and respiration. CONCLUSIONS: Speech and gait deficits in PD may share a common mechanism in the underlying cortical circuits. Further, rSLT was more beneficial to dysrhythmic PD patients than rBMT, likely because of the nature of the rhythmic cue.